Job insecurity is associated with presenteeism, but not with absenteeism: A study of 19 720 full‐time waged workers in South Korea - Kim, Ji‐Hwan (J Occup Health, 2020)
OBJECTIVE: This study examined whether perceived job insecurity was associated with absenteeism and presenteeism, and how these associations varied when the differential cutoff was applied to define absenteeism and presenteeism. METHODS: We analyzed a nationally representative dataset of 19 720 full‐time waged workers from the 4th Korean Working Conditions Survey (2014). As an independent variable, perceived job insecurity was assessed. As dependent variables, absenteeism and presenteeism were measured. Seven differential cutoffs (from “1 day” to “7 days”) were used when defining absenteeism and presenteeism. A Poisson regression model with a robust error variance was applied for the analysis. RESULTS: When “1 day” was cutoff to define absenteeism and presenteeism, job insecurity was not associated with both absenteeism (PR: 1.07, 95% CI: 0.97, 1.16) and presenteeism (PR: 1.05, 95% CI: 1.00, 1.10). When the higher cutoff was used, the association between job insecurity and absenteeism was attenuated and remained statistically nonsignificant. However, statistically significant associations between job insecurity and presenteeism were observed when the differential cutoff was used: “2 days” (PR: 1.07, 95% CI: 1.01, 1.13), “3 days” (PR: 1.14, 95% CI: 1.06, 1.22), “4 days” (PR: 1.15, 95% CI: 1.05, 1.26), “5 days” (PR: 1.18, 95% CI: 1.06, 1.30), “6 days” (PR: 1.17, 95% CI: 1.02, 1.33), and “7 days” (PR: 1.17, 95% CI: 1.02, 1.34). CONCLUSION: This study found that perceived job insecurity was associated with presenteeism, but not absenteeism. Furthermore, the association differed by cutoff applied to define presenteeism among full‐time waged workers in South Korea.